THE EMOTIONAL EXPERIENCES OF SENIOR HIGH SCHOOL STUDENTS IN LEARNING ENGLISH USING ONLINE PLATFORM DURING THE COVID-19 - Nurlita Malota; Mukrim Mukrim; Zarkiani Hasyim (e-Journal of ELTS (English Language Teaching Society), 2022)
The aim of this study was to find out the emotional experiences of students in online learning English using online platform in the middle of Covid-19. The research was a single case study. Data were garnered from the results of interviews and document. The participants in this study were three students at SMAN 3 Luwuk. The researchers analyzed the data thematically as proposed by Braun & Clarke, 2006. The finding showed that online learning English affected the emotional experiences of the students. The students experienced such positive emotions as happiness. The happiness came from the teacher who provided feedback and explanation before giving tasks, allowed the students to send their tasks on platform they wanted, explained the material through Zoom, and did not provide tasks in each meeting. However, they also experienced such negative emotions as frustration, anger, and anxiety in English learning using online platform. They perceived frustration because of online English learning was difficult for them. The difficulties were the students had to purchase internet quota, not meeting in person with the teacher, having limitation of time, feeling bored due to always use Zoom, getting much disturbance, and their memory filled up fast because of getting many files from their teachers. Thus, the negative emotions decreased the students’ time invested and the amount of knowledge gained from learning process. The cause of positive feeling was teachers. Meanwhile, the negative feelings were caused by internet quota expenses and internet connection.